GNSS solutions for increased ga and rotorcraft airport accessibility demonstration - Schmerwitz, S.; Dautermann, T.; Lenz, H.; Lueken, T. (My University, 2019)
Within the framework of the SESAR programme concepts were developed to integrate general aviation aircraft and rotorcraft into the airspace and airports without influencing the main traffic flow. On the one hand this paper discusses the idea of a low-level route network to allow IFR operations separately from the regular routing. On the other hand the concept of simultaneous non-interfering approaches is presented to guide these aircraft to or from a point in space located at a final approach and take-off area from which it can continue visually to land. Both concepts have been evaluated in real-time simulations by DLR in preparation for a flight trial. The exercise will be explained in detail and the results show that operational concepts should work. It is concluded to continue the process of implementing these concepts and advised to enable safer flight by further promoting advanced point-in-space procedures.